2011
DOI: 10.3324/haematol.2011.050815
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen tension plays a critical role in the hematopoietic microenvironment in vitro

Abstract: BackgroundIn the bone marrow mesenchymal stromal cells and osteoblasts form functional niches for hematopoietic stem and progenitor cells. This microenvironment can be partially mimicked using in vitro co-culture systems. In this study, we examined the oxygen tension in three distinct compartments in a co-culture system of purified CD34 + cells and mesenchymal stromal cells with regard to different spatial localizations. Design and MethodsHypoxic cells in the co-culture were visualized by pimonidazole staining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 42 publications
(49 reference statements)
0
46
1
Order By: Relevance
“…Indeed, within the bone marrow structure, haematopoietic stem cells are found sequestered in regions staining most strongly for the hypoxia probe pimonidazole, a 2-nitroimidazole compound, which forms covalent bonds with cellular macromolecules at oxygen levels below 1.3 kPa. Taken together with the evidence that low oxygen tensions favour the maintenance of haematopoietic stem cells in culture [20], hypoxia appears to play a critical role in neutrophil development.…”
Section: Relevance Of Hypoxia To Neutrophilsmentioning
confidence: 82%
“…Indeed, within the bone marrow structure, haematopoietic stem cells are found sequestered in regions staining most strongly for the hypoxia probe pimonidazole, a 2-nitroimidazole compound, which forms covalent bonds with cellular macromolecules at oxygen levels below 1.3 kPa. Taken together with the evidence that low oxygen tensions favour the maintenance of haematopoietic stem cells in culture [20], hypoxia appears to play a critical role in neutrophil development.…”
Section: Relevance Of Hypoxia To Neutrophilsmentioning
confidence: 82%
“…Many groups have shown that co-culture of leukemic cells with BMSC or OB provides a survival advantage when challenged with chemotherapy agents 9,10,[12][13][14][19][20][21] . Work modeling normal immature CD34+ hematopoietic cells in coculture with mesenchymal stem cells (MSC) revealed that hematopoietic cells will interact with the adherent monolayer of MSCs to form three distinct spatial populations of hematopoietic cells 22,23 . Proliferation and differentiation of the CD34+ cells was effected relative to their location within the co-culture 22 .…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Leukemic cells can infiltrate the niches leading to their enhanced self-renewal and proliferation, quiescence and resistance to chemotherapeutic agents. 7,8 Hypoxia is, therefore, associated with poor prognosis in leukemia, especially in acute myeloid leukemia (AML), [9][10][11][12][13] as also described in cancer and inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%